Etika dan Moralitas Pada Media Sosial Dalam Prespektif Hadis : (Studi Analisis Hadis Tentang Flexing) - Muhammad Sowi Sowi; Lalu Turjiman Ahmad lalu (Department of Ilmu al-Qur'an dan Tafsir, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2023)
Ethics and morality on social media are something that must be paid attention to, where a phenomenon called flexing has become a topic of discussion because it is not really in line with the culture of ethics and morality. The results of this research are formulating hadiths related to flexing through primary sources of hadith books in a thematic pattern and the opinion of hadith scholars regarding these flexing hadiths is to tell us all to always be careful in doing anything, especially on social media nowadays, contextualizing this flexing hadith with ethical behavior and morality on today's social media, where some of its activists carry out acts of showing off luxury.